2012
DOI: 10.1021/ja302121z
|View full text |Cite
|
Sign up to set email alerts
|

Primary Events in the Blue Light Sensor Plant Cryptochrome: Intraprotein Electron and Proton Transfer Revealed by Femtosecond Spectroscopy

Abstract: Photoreceptors are chromoproteins that undergo fast conversion from dark to signaling states upon light absorption by the chromophore. The signaling state starts signal transduction in vivo and elicits a biological response. Therefore, photoreceptors are ideally suited for analysis of protein activation by time-resolved spectroscopy. We focus on plant cryptochromes which are blue light sensors regulating the development and daily rhythm of plants. The signaling state of these flavoproteins is the neutral radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
115
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 77 publications
12
115
1
1
Order By: Relevance
“…Type I Cryptochromes-The decisive steps of signal generation in the plant cryptochrome between the initial ultrafast electron transfer to FAD (14) and the structural change in the CCT (24,25) are unclear. In particular, the role of the proton transfer to the flavin radical needs to be elucidated considering the fact that the aspartic acid close to flavin is exclusively present in the plant cryptochrome.…”
Section: The Role Of the Flavin Anion Radical In Plant And Animalmentioning
confidence: 99%
See 3 more Smart Citations
“…Type I Cryptochromes-The decisive steps of signal generation in the plant cryptochrome between the initial ultrafast electron transfer to FAD (14) and the structural change in the CCT (24,25) are unclear. In particular, the role of the proton transfer to the flavin radical needs to be elucidated considering the fact that the aspartic acid close to flavin is exclusively present in the plant cryptochrome.…”
Section: The Role Of the Flavin Anion Radical In Plant And Animalmentioning
confidence: 99%
“…Much less is known about the role of the subsequent step of proton transfer to flavin. In plant cryptochromes, this step is unusually separated in time from the initiating electron transfer by 6 orders of magnitude (14,15). A much faster proton transfer has been postulated in theoretical studies (31), but indications for such a competing process have been found only to some extent above the physiological pH (pH 7.4) and in the absence of ATP (32).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…•+ ], on the other hand, can persist for as long as microseconds [1,[12][13][14] -long enough to allow the yield of the signalling state to depend on the direction of an Earth-strength magnetic field. The identity of this long-lived form of the protein is uncertain; the assumption is that it passes on magnetic information via a conformational change in the C-terminal domain [15].…”
Section: Introductionmentioning
confidence: 99%